One-step reconstruction of assembled 3D holographic scenes - Velez Zea, Alejandro (2015)
We present a new experimental approach for reconstructing in one step 3D scenes otherwise not feasible in a single snapshot from standard off-axis digital hologram architecture, due to a lack of illuminating resources or a limited setup size. Consequently, whenever a scene could not be wholly illuminated or the size of the scene surpasses the available setup disposition, this protocol can be implemented to solve these issues. We need neither to alter the original setup in every step nor to cover the whole scene by the illuminating source, thus saving resources. With this technique we multiplex the processed holograms of actual diffuse objects composing a scene using a two-beam off-axis holographic setup in a Fresnel approach. By registering individually the holograms of several objects and applying a spatial filtering technique, the filtered Fresnel holograms can then be added to produce a compound hologram. The simultaneous reconstruction of all objects is performed in one step using the same recovering procedure employed for single holograms. Using this technique, we were able to reconstruct, for the first time to our knowledge, a scene by multiplexing off-axis holograms of the 3D objects without cross talk. This technique is important for quantitative visualization of optically packaged multiple images and is useful for a wide range of applications. We present experimental results to support the method.